Analisis Ketertarikan Wakaf Generasi Muda dengan Teknologi Acceptance Model - Putri Ramadhanty Ningtias; Prameswara Samofa Nadya (Perbanas Journal of Islamic Economics and Business, 2022)
Based on CAF World Giving Index 2021, Indonesia is the most generous country in the world, with the highest donor index. Supported by a high number of Moslems, there is a high potential for growth of Islamic philanthropy. Waqf as a form of Islamic philanthropy is currently still underdeveloped. One of the contributing factors is the lack of socialization. The purpose of this study was to analyze the interests of generations Y and Z both as a donator of berkahwakaf.id site with a technology acceptance model (TAM) approach. This research design uses associative research with a quantitative approach using data of 100 respondents as sample, analyzed with PLS method. The results showed that perceived benefits had a significant positive effect on interest, while user convenience had a significant negative effect on interest. Attitude has a significant positive effect on interest, usefulness has a positive effect on attitudes, while user convenience has a significant negative effect.